2019
DOI: 10.1186/s13613-019-0597-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-flow nasal cannula and non-invasive ventilation on inspiratory effort in hypercapnic patients with chronic obstructive pulmonary disease: a preliminary study

Abstract: BackgroundNon-invasive ventilation (NIV) is preferred as the initial ventilatory support to treat acute hypercapnic respiratory failure in patients with chronic obstructive pulmonary disease (COPD). High-flow nasal cannula (HFNC) may be an alternative method; however, the effects of HFNC in hypercapnic COPD are not well known. This preliminary study aimed at assessing the physiologic effects of HFNC at different flow rates in hypercapnic COPD and to compare it with NIV.MethodsA prospective physiologic study en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 29 publications
2
51
0
1
Order By: Relevance
“…In this regard, our study is different from other studies initiating the oxygen support to ARF patients with HFNC on admission. The study conducted by Rittayamai et al explored flow rates' effect on respiratory workload and also found that 30 lt/min had better outcomes than lower flow rates [13]. While other studies showing gradually increased flow rates might be beneficial, due to the retrospective method, we could not specify which patients might benefit from different rates of flow.…”
Section: Discussionmentioning
confidence: 89%
“…In this regard, our study is different from other studies initiating the oxygen support to ARF patients with HFNC on admission. The study conducted by Rittayamai et al explored flow rates' effect on respiratory workload and also found that 30 lt/min had better outcomes than lower flow rates [13]. While other studies showing gradually increased flow rates might be beneficial, due to the retrospective method, we could not specify which patients might benefit from different rates of flow.…”
Section: Discussionmentioning
confidence: 89%
“…During exacerbation of COPD, higher than usual patient’s inspiratory flow demand requires an increase of flow setting with HFNC. In 12 hypercapnic patients with COPD initially treated with noninvasive ventilation, Rittayamai and colleagues achieved similar work of breathing with HFNC flow set at 30 L/min [ 65 ]. Discontinuing HFNC to use a facemask significantly increased patients’ breathing efforts [ 66 ].…”
Section: Clinical Implications and Recommendations: Trans-nasal Aerosmentioning
confidence: 99%
“…Furthermore, caregiver skill is important to the success of this technique. High-flow nasal cannula may be an alternative method [77,78].…”
Section: New Avenues Of Researchmentioning
confidence: 99%
“…High-flow nasal cannula may be an alternative method [ 77 , 78 ]. In a recent study conducted in 12 hypercapnic COPD patients with mild to moderate exacerbation who had initially required NIV, applying high-flow nasal cannula at 30 l/min for a short duration reduced inspiratory effort, and resulted in an effect similar to that of NIV delivered at moderate levels of pressure support [ 78 ]. In addition, high-flow nasal cannula is a more comfortable technique than NIV [ 79 , 80 ].…”
Section: New Avenues Of Researchmentioning
confidence: 99%